INFLUENCE OF THIOPENE ON THE CONVERSION OF METHYL-CYCLOPENTANE AND N.HEXANE TO BENZENE USING MONO-AND BI-METALLIC REFORMING CATALYSTS - A.S. Nasution (Scientific Contributions Oil and Gas, 2004)
Parrafin and naphthene hydrocarbons are usually the major component in the naptha reforming feedstock. Thus the conversion of these hydrocarbon to high octane motor gasoline and aromatic hydrocarbon is one of the important reactions of the catalytic reforming process, (Montamal., 1965). And aromatization reaction is guided by both metal and acid sites of bi-functional reforming catalyst (Hobson 1973).